Social workers in Lebanon facing the meaning of social work: A study highlighting the meaning of social work for the professionals who are practicing this work in a diverse and complicated context - Nemer, Sana Elias (Edelweiss Applied Science and Technology, 2025)
This study aims to unveil the meaning of social work as perceived by social workers in Lebanon. This meaning was explored through the expressions of 29 surveyed social workers. Their understanding of this meaning was influenced by both personal and professional factors. This meaning emerged from a dynamic, interactive process between the social workers and their work, resulting in feelings of satisfaction, motivation, commitment, pleasure, or suffering as a product. This study sheds new light on a work context, such as the Lebanese context, which has suffered from diverse and complicated problems for years. This is qualitative research with symbolic interactionism as the epistemological framework. The research was conducted in Beirut and the Mount Lebanon regions. Data was collected through semi-structured individual interviews, then transcribed and analyzed using content analysis. The study’s findings reveal several dimensions of meaning in social work experienced by practitioners, directly influenced by their interactions within a complex and unstable work environment. Despite these challenges, social workers consistently identify sources of satisfaction and motivation, enabling them to adapt and sustain their dedication to the profession. These insights offer pathways for future research, given the limited national-level studies on social work within this specific context.